Supramolecular heptanuclear Ln–Cu complexes involving nitronyl nitroxide biradicals: structure and magnetic behavior. Issue 17 (22nd April 2022) - Xi, Lu; Jin, Chao-Yi; Song, Hong-Wei; Wang, Xiao-Tong; Li, Li-Cun; Sutter, Jean-Pascal
Abstract : Supramolecular heptanuclear 2p–3d–4f complexes have been achieved using a nitronyl nitroxide biradical and the CuDy analogue exhibits magnetic relaxation behavior. Abstract : Four novel heptanuclear Ln–Cu complexes with the formula [Ln2 Cu(hfac)8 (NITPhTzbis)2 ][LnCu(hfac)5 (NITPhTzbis)]2 (LnCu = YCu 1, TbCu 2, DyCu 3 and HoCu 4 ; hfac = hexafluoroacetylacetonate) were successfully constructed by employing the triazole functionalized nitronyl nitroxide biradical ligand NITPh-Tzbis (NITPh-Tzbis = 5-(1, 2, 4-triazolyl)-1, 3-bis(1′-oxyl-3′-oxido-4′, 4′, 5′, 5′-tetramethyl-4, 5-hydro-1 H -imidazol-2-yl)benzene). These hetero-tri-spin complexes are composed of two biradical-bridged dinuclear [(LnCu(hfac)5 (NITPhTzbis)] units and one trinuclear [Ln2 Cu(hfac)8 (NITPhTzbis)2 ] unit which form a heptanuclear supramolecular structure through π–π interactions. Magnetic susceptibility investigations indicate that ferromagnetic exchange interactions dominate at low temperature for this supramolecular system which can be attributed to the Ln–nitroxide exchange and intramolecular NIT⋯NIT coupling mediated by the m -phenylene moiety. The DyCu derivative was found to exhibit a slow magnetic relaxation behavior.